Tashmîm Al-Mu’jam Al-Mushôhib li Al-Kitâb Al-‘Arabiyah li An-Nâsyiîn ‘ala Asâs Al-Madkhol As-Siyaqî fî Ma’had Muhammadiyah Al-Islâmî ‘Abdu Ar-Razzâq Fakhru Ad-Dîn Yogyakarta - Muliawati, Harum; Mufarokah, Siti; Mahbub, Mohammad (Ukazh: Journal of Arabic Studies, 2024)
أن تصميم المعجم من لوازم العملية لضرورته ونفعته الكثيرة فهو أيضا يتميز بالغنى والتنوع، ولأن هذا الغنى لم يتجسد على مستوى الكمي فحسب، وإنما كذلك على صعيد الكيف. يهدف هذا البحث إلى إنتاج المعجم المصاحب لكتاب العربية للناشئين على أساس المدخل السياقي في معهد محمدية الإسلامي عبد الرزاق فخر الدين يوكياكرتا. هذا البحث هو البحث والتطوير من نموذج (ADDIE) وهو: تحليل الاحتياجات، التصميم، التطوير، التجربة، التقويم. أما جمع البيانات فيكون بطريقة الملاحظة، والمقابلة، والاستبانة، وكذا دراسة الوثائق. ونتيجة هذا البحث هي إن تصميم المعجم المصاحب لكتاب العربية للناشئين على أساس المدخل السياقي بدأ من تحليل الاحتياجات والمشكلات ثم تصميم المعجم المصاحب على أساس المدخل السياقي ثم تصميم المعجم المصاحب على أساس المدخل السياقي ثم تجربة المعحم المصاحب على أساس المدخل السياقي ثم التقويم من قبل الخبراء والطلبة The design of the dictionary is one of the requirements of the process due to its necessity and many benefits. It is also characterized by richness and diversity, and because this richness is not only embodied on the quantitative level, but also on the qualitative level.. This research aims to produce the accompanying dictionary for the Arabic book for young people based on the contextual approach at the Muhammadiyah Islamic Institute Abdul Razzaq Fakhruddin Yokyakarta. This research is the research and development of a model (ADDIE) It is: needs analysis, design, development, experimentation, and evaluation. Data collection is done by observation, interview, questionnaire, and document study. The result of this research is that designing the accompanying dictionary for the Arabic book for young people on the basis of the contextual approach started from analyzing the needs and problems, then designing the accompanying dictionary on the basis of the contextual approach, then designing the accompanying dictionary on the basis of the contextual approach, then experimenting with the accompanying dictionary on the basis of the contextual approach, then evaluation by experts and students. Perancangan kamus merupakan salah satu syarat proses karena kebutuhannya dan banyak manfaatnya, juga ditandai dengan kekayaan dan keragaman, dan karena kekayaan ini tidak hanya diwujudkan pada tataran kuantitatif, tetapi juga pada tataran kualitatif. Penelitian ini bertujuan untuk menghasilkan Kamus Pendamping Kitab Arab untuk Remaja Berbasis Pendekatan Kontekstual di Institut Agama Islam Muhammadiyah Abdul Razzaq Fakhruddin Yokyakarta. Penelitian ini merupakan penelitian dan pengembangan model (ADDIE) Yaitu: analisis kebutuhan, desain, pengembangan, eksperimen, dan evaluasi. Pengumpulan data dilakukan dengan observasi, wawancara, angket, dan studi dokumen. Hasil dari penelitian ini adalah merancang kamus pendamping kitab berbahasa arab untuk remaja berdasarkan pendekatan kontekstual yang dimulai dari menganalisis kebutuhan dan permasalahan, kemudian merancang kamus pendamping berdasarkan pendekatan kontekstual, kemudian merancang kamus pendamping kamus berdasarkan pendekatan kontekstual, kemudian bereksperimen dengan kamus pendamping berdasarkan pendekatan kontekstual, kemudian evaluasi oleh ahli dan siswa.